O Geometrycznie Nieliniowej Teorii Powłok Lepkosprężystych - Bielewicz, E. (Engineering Transactions, 1966)
This paper is concerned with quasi-static problems of isotropic visco-elastic shells under the action of an external load and a steady temperature field. The fundamental equations of the problem are derived in brief, making use of a number of simplifying assumptions, the most important of which are as follows. 1) The deformation is small except the displacement component normal to the middle surface of the shell the value of which is finite but small as compared with the dimensions of the shell, 2) The Kirchhoff-Love assumption is valid, 3) The physical relations are linear.